The Effect of Organizational Commitment and Organizational Citizenship Behavior Toward Service Quality at Universitas Kristen Indonesia - Edison Siregar; Muchlis R. Luddin; Thomas Suyatno (Program Studi S3 Ilmu Manajemen, 2019)
The objective of this research is to find out the effect organizational commitment and organizational citizenship behavior towards service quality at Universitas Kristen Indonesia. The research method used was a quantitative method wiht using path analysed design. In collecting the data, 71 employees were chosen from 243 employees randomly to be the sample of this research. The data of the this research were obtained by distrubuting questiinnaires and analyzed them using path analysis. The result shows that there exists a positive direct effect of (1) organizational commitment towards service quality, (2) organizational citizenship behavior towards service quality, and (3) organizational commitment towards organizational citizenship behavior. Therefore, as the conclussion to this research, to improve the service quality of the employee at Universitas Kristen Indonesia, the organizational commitment, and organizational citizenship behavior should be improved.